2005
DOI: 10.1007/s00426-004-0202-9
|View full text |Cite
|
Sign up to set email alerts
|

Can the location negative priming process operate in a proactive manner?

Abstract: The location negative priming (NP) effect refers to the fact that the processing of a current target stimulus (probe trial) is delayed when it appears at a location that has recently contained a distractor event (prime trial), relative to when it occurs at a previously unoccupied position. One view is that the process causing the NP effect involves the inhibition of the internal representation of the prime-distractor event, and that the future processing of target stimuli that involve this event are prolonged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 20 publications
2
21
1
Order By: Relevance
“…For the 750 ms probe delay, consistent with prior work (e.g., Buckolz et al, 2006;; Experiment 1), distractor-repeat reactions (RT = 442 ms) matched those produced by the control trials (RT = 446 ms). For the 75 ms probe onset delay, probe target reactions were signiWcantly faster when the probe distractor re-appeared at its prime-trial location (distractor-repetition RT = 447 ms) than when it showed up at a new location (control RT = 475 ms), more so for the distractor-or-target prime.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…For the 750 ms probe delay, consistent with prior work (e.g., Buckolz et al, 2006;; Experiment 1), distractor-repeat reactions (RT = 442 ms) matched those produced by the control trials (RT = 446 ms). For the 75 ms probe onset delay, probe target reactions were signiWcantly faster when the probe distractor re-appeared at its prime-trial location (distractor-repetition RT = 447 ms) than when it showed up at a new location (control RT = 475 ms), more so for the distractor-or-target prime.…”
Section: Resultssupporting
confidence: 81%
“…The diVerent contexts (prime-trial types) within which prime distractor events were processed in this study did not alter how earlier distractor-occupied locations inXuenced later distractor processing at the same location. Two, the similar latencies seen for the distractor-repeat than for the control trials (e.g., see Buckolz et al, 2006;; but see Christie & Klein, 2001) argues against speculation that one useful function possibly performed by the spatial NP process would be to produce a more expeditious elimination of future distractor events when they show up at the same location on consecutive trials (e.g., Buckolz et al, 2002;Christie & Klein, 2001). Had this been the case, probe target latencies would have been faster on distractor-repeat than on control trials.…”
Section: Probe-trial Reaction Timementioning
confidence: 76%
See 2 more Smart Citations
“…In fact, studies that did not permit the omitting of a cued distractor location from the search array have not shown any indication of inhibition. In Chao (2010), as well as in Buckolz, Guy, Khan, and Lawrence (2006), participants were cued with one of four display locations as the location of the distractor with 67% validity. The target could still appear in any of the four display locations with equal probability.…”
Section: Resilience Of the Awb Effectmentioning
confidence: 99%